STRATEGI INVESTASI PADA RUMAH TANGA PETANI TRADISIONAL DI KECAMATAN MAPATTUNGGUL SELATAN - Yulhendri, Yulhendri; Kurniawati, Tri; Susanti, Nora (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
Analyzing households investment behavior in remote environments is attractively conducted as a scientific effort to tackle the problem of poverty in the long term. The population of study was households located in remote areas in Pasaman Regency, district of South Mapattunggul. It is about 1,991 heads of household. The sample is 307  households which are formulated by using Slovin formula. This study uses multiple regression analysis and qualitative analysis on mixed method perspective. Investment behavior in traditional farming households in the District of South Mapattunggul is influenced by consumer behavior, knowledge, hope the old days, learning, price, and level of education. Partially, learning process and life expectation do not affect the investment behavior. Knowledge of pricing information has a negative correlation with the investment. It means that the higher the price, or the risks they run, the lower investments. This is in line with the general logic that the higher the risk, the less people are willing to enter into an investment.   Society is mainly prioritizing daily consumption as the main priority use of their revenue when the prices are high.Community learning process does not consistently affect the investment behavior including expectations of the old days.  It is caused by lower educational facilities and low level of households expectations in improving their old days lives.